Sol-gel polymerization of silylated amino acids around a protein template yields selective biomimetic imprints. (January 2023) - Gutiérrez-Climente, R.; Ngo, G.; Clavié, M.; Gouyon, J.; Ladner, Y.; Etienne, P.; Dumy, P.; Perrin, C.; Mehdi, A.; Martineau, P.; Pugniére, M.; Subra, G.
Abstract: The development of artificial receptors able to selectively recognize a target protein is of particular interest in separation, diagnostics, and therapeutics fields. Herein, we disclose a method to prepare biomimetic and functionalized protein imprints in biocompatible conditions avoiding any protein denaturation. For that purpose, a set of different hybrid silylated amino acid derivatives were synthesized and used without tetraethyl orthosilicate to prepare our molecularly imprinted polymers, allowing to reduce to a minimum of the silicon amount, in order to obtain imprints made almost entirely of amino acids to mimic paratope surfaces of antibodies. Such functional building blocks were polymerized on the surface of magnetic silica nanoparticles at pH 8.5 in ultrapure water in the presence of two globular proteins: cytochrome C or lysozyme. The resulting imprinted hybrid materials were evaluated for their adsorption capacity, specificity, and selectivity by quartz-crystal microbalance with dissipation and magnetic enzyme-linked immunosorbent assay (ELISA) assays. High imprinting factors of 8.7 were measured for these biomimetic hybrid materials (corresponding to approximately 4000 and 450 ng of protein per cm 2 immobilized on molecularly imprinted polymers and non-imprinted polymer nanoparticles, respectively), representing a significant breakthrough in sol-gel-based molecular imprinting materials. Moreover, competition experiments performed by magnetic ELISA (mELISA) show very good specificity of our imprints at the usual concentrations of ELISA measurements.